2021
DOI: 10.3390/foods10020359
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Oil Attenuates Chronic Inflammation by Inducing M2 Macrophage Switching in High-Fat Diet-Fed Obese Mice

Abstract: Macrophages are involved in all inflammatory processes from killing pathogens to repairing damaged tissue. In the obese state, macrophages infiltrate into enlarged adipose tissue and polarize into pro-inflammatory M1 macrophages, resulting in chronic low-grade inflammation due to the secretion of inflammatory mediators. Rice bran oil (RBO) is an edible oil containing tocopherols, tocotrienols, and γ-oryzanol. Previous research in normal diet-fed mice suggested that RBO mitigates inflammatory responses by modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…RO and BO also contain high levels of micronutrients, such as γ‐oryzanol, phytosterols and squalene. γ‐Oryzanol may have anti‐inflammatory effects by causing appropriate macrophage polarization and reducing the secretion of pro‐inflammatory factors by macrophages 53,54 . Phytosterols and squalene inhibit the production of inflammatory enzymes and pro‐inflammatory cytokines by reducing nuclear factor‐kappa B expression 55,56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RO and BO also contain high levels of micronutrients, such as γ‐oryzanol, phytosterols and squalene. γ‐Oryzanol may have anti‐inflammatory effects by causing appropriate macrophage polarization and reducing the secretion of pro‐inflammatory factors by macrophages 53,54 . Phytosterols and squalene inhibit the production of inflammatory enzymes and pro‐inflammatory cytokines by reducing nuclear factor‐kappa B expression 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…γ-Oryzanol may have anti-inflammatory effects by causing appropriate macrophage polarization and reducing the secretion of pro-inflammatory factors by macrophages. 53,54 Phytosterols and squalene inhibit the production of inflammatory enzymes and pro-inflammatory cytokines by reducing nuclear factor-kappa B expression. 55,56 Furthermore, in the www.soci.org L Yang et al…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the density of vessels with smooth muscle wall was decreased on GBD, suggesting attenuation of arteriogenesis. This effect can be mediated via changes of inflammatory state on GBD, known to affect arteriogenesis (52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…RBO supplementation improved the anti-inflammatory status (increased the IL-10 level and decreased the IL-6 and TNF-α levels) in bone marrow-derived macrophages. The study showed that RBO could improve obesity-induced chronic inflammation by altering the expression of inflammation-associated markers and macrophage polarization [ 100 ].…”
Section: Anti-obesity Properties Of Rice Branmentioning
confidence: 99%
“…The overall host inflammatory system was improved during RB supplementation. In particular, C-RP, TNF-α, COX-2, VCAM-1, IL-6, and IL-1β levels were improved in serum and adipose tissue and improved vascular and microvascular inflammation [ 86 , 87 , 89 , 100 ]. Moreover, RB supplementation improved the expression of IRS-2 (insulin receptor), GLUT-2 (glucose transporter), and glucokinase in the pancreas [ 96 ], glucose–insulin homeostasis [ 97 ], and reduced the pancreatic islet size and pancreatic insulin [ 98 ].…”
Section: Mechanisms Associated With the Anti-obesity Property Of Rice...mentioning
confidence: 99%